2010
DOI: 10.1016/j.ajog.2009.11.021
|View full text |Cite
|
Sign up to set email alerts
|

The incidence of urinary incontinence across Asian, black, and white women in the United States

Abstract: Objective-We calculated incidence rates of urinary incontinence by incontinence frequency and type over 4 years in Asian, black, and white women in the United States.Study Design-Prospective analyses included 76,724 participants aged 37-79 years in the Nurses' Health Study cohorts with no incontinence at baseline.Results-The 4-year incidence of incontinence at least monthly was higher in white women (7.3/100 person-years) compared with Asian (5.7/100 person-years, p=0.003) and black women (4.8/100 person-years… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
39
0
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(44 citation statements)
references
References 38 publications
3
39
0
2
Order By: Relevance
“…There seem to be ethnic differences. Asian women were less prone to UI or LUTS, which is in line with a global prevalence analysis by Milsom et al [23] and an incidence study by Townsend et al [24]. Some of the differences observed can probably be E U R O P E A N U R O L O G Y X X X ( 2 0 1 4 ) X X X -X X X attributed to methodological differences among studies.…”
Section: Discussionsupporting
confidence: 80%
“…There seem to be ethnic differences. Asian women were less prone to UI or LUTS, which is in line with a global prevalence analysis by Milsom et al [23] and an incidence study by Townsend et al [24]. Some of the differences observed can probably be E U R O P E A N U R O L O G Y X X X ( 2 0 1 4 ) X X X -X X X attributed to methodological differences among studies.…”
Section: Discussionsupporting
confidence: 80%
“…According to data from NHANES, 12.3% of black women report SUI as compared to 26.5% of white or 25.8% of Mexican-American women (OR for SUI in white vs black women: 2.79) [9]. Similar results recently have been reported for women in the BACH survey [10], in the NHS [25], within the U.S. military health system [26], and those living in the state of Michigan [27]. Physiologic differences to explain racial variation in prevalence have not been well studied [1, 4‱‱].…”
Section: Effects Of Age Race and Pregnancy On Prevalencesupporting
confidence: 71%
“…Considering that pelvic floor dysfunctions indicate laxity of the component tissues, some authors have identified differences in the prevalence of these dysfunctions according to race/ethnicity [29,30]. In contrast, other investigators failed to observe this finding [24].…”
Section: Discussionmentioning
confidence: 99%